2021
DOI: 10.1136/bmj-2021-066381
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pathological complete response as surrogate endpoint in neoadjuvant randomised clinical trials of early stage breast cancer: systematic review and meta-analysis

Abstract: Objective To evaluate pathological complete response as a surrogate endpoint for disease-free survival and overall survival in regulatory neoadjuvant trials of early stage breast cancer. Design Systematic review and meta-analysis. Data sources Medline, Embase, and Scopus to 1 December 2020. Eligibility criteria for study selection Randomised clinical trials that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 94 publications
2
50
0
Order By: Relevance
“…The prognostic value of pCR is found across breast cancer subtypes, but is highest in triple negative and HER2-positive breast cancer [ [20] , [21] , [22] ]. However, a large and more recent published meta-analysis including 54 randomized trials did not find a strong association between pCR and disease-free survival [ 23 ]. Although the analysis was not based on individual patient data and results were not stratified within HER2-positive subgroups the findings stress the need for supportive real-world evidence of survival benefit for agents approved and widely prescribed following trials powered for surrogate endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of pCR is found across breast cancer subtypes, but is highest in triple negative and HER2-positive breast cancer [ [20] , [21] , [22] ]. However, a large and more recent published meta-analysis including 54 randomized trials did not find a strong association between pCR and disease-free survival [ 23 ]. Although the analysis was not based on individual patient data and results were not stratified within HER2-positive subgroups the findings stress the need for supportive real-world evidence of survival benefit for agents approved and widely prescribed following trials powered for surrogate endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…More significantly, our results showed that TNAC patients have a poor chemotherapy responsiveness and no benefit from chemotherapy in terms of BCSS. Previous studies showed that pCR can be used as a surrogate endpoint in TNBC patients receiving neoadjuvant chemotherapy, meaning that patients who reached pCR have better survival than those who did not reach pCR [ 35 , 36 , 37 , 38 , 39 , 40 ]. Among the four molecular subtypes of TNBC, the LAR group has the lowest pCR rate [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…When ascertaining the benefits of cancer medicines through HTA, improvements in surrogate measures would need to be translated into OS or QoL estimates, extrapolated over time and inform key metrics for HTA, including cost-effectiveness. Such transformation and extrapolation can add substantial uncertainty to the assessment, as their robustness is subject to the assumptions used and the selected methodologies [ 40 , 41 , 42 , 43 , 44 ]. For example, a methodology review assessing the validity of PFS as a surrogate endpoint for predicting OS in cancer clinical trials found wide heterogeneity in methods and reporting [ 29 ].…”
Section: Challenges Relating To Clinical Trial Datamentioning
confidence: 99%